Magnus management consultants the survival dilemma - Choo, Kok Meng (1999)
This case study outlines the dilemma that the management of Magnus Management Consultants, a Dutch based management consulting company whose Asian operations headquarters was based in Kuala Lumpur, Malaysia, faced during the recessionary period in Asia during the period 1997 to 1999. Faced with stiff competition from both local and international consulting firms in terms of consulting fees, and the ever shrinking ERP market share, the company faces a big hurdle to maintain its existence in the market. The analysis section details the strategies that the company could employ to bring itself out of the doldrums with options for a cheaper and diversified services to expand vertically with more services to tap into new market segments and contine generating revenue from existing installed bases while keeping its operations costs down. The strategies also attempt to prepare the company to face the different scenarios which could happen and have a negative impact on the company's survival factor.